2014
DOI: 10.1038/bmt.2014.257
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell reconstitution is associated with relapse-free survival and acute GVHD severity in children after allogeneic stem cell transplantation

Abstract: DCs are potent APCs and key regulators of innate and adaptive immunity. After allo-SCT, their reconstitution in the peripheral blood (PB) to levels similar to those in healthy individuals tends to be slow. We investigate the age-and sex-dependant immune reconstitution of myeloid (mDC) and plasmacytoid DC (pDC) in the PB of 45 children with leukaemia or myelodysplastic syndrome (aged 1-17 years, median 10) after allo-SCT with regard to relapse, acute GVHD (aGVHD) and relapse-free survival. Low pDC/μL PB up to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 61 publications
1
9
1
Order By: Relevance
“…Relatively low pDC levels at days 0 to 60 after HCT are associated with moderate to severe aGVHD in children, which is in line with observations in adults [54][55][56]. On the other hand, high pDC peak levels at days 0 to 60 are associated with higher risk of relapse, whereas high overall levels of both cDCs and pDCs during the first 200 days after HCT are related to higher relapse-free survival (evaluated as the area under the curve of z-score graphs where a high initial pDC level would lead to a reduced z-score over a longer period of time) [38]. As DCs play an instrumental role in the initiation of immune responses and maintenance of homeostasis, the use of the presence and activation state of DC subsets as biomarkers may be included in future studies.…”
Section: Dendritic Cellssupporting
confidence: 87%
See 2 more Smart Citations
“…Relatively low pDC levels at days 0 to 60 after HCT are associated with moderate to severe aGVHD in children, which is in line with observations in adults [54][55][56]. On the other hand, high pDC peak levels at days 0 to 60 are associated with higher risk of relapse, whereas high overall levels of both cDCs and pDCs during the first 200 days after HCT are related to higher relapse-free survival (evaluated as the area under the curve of z-score graphs where a high initial pDC level would lead to a reduced z-score over a longer period of time) [38]. As DCs play an instrumental role in the initiation of immune responses and maintenance of homeostasis, the use of the presence and activation state of DC subsets as biomarkers may be included in future studies.…”
Section: Dendritic Cellssupporting
confidence: 87%
“…Associations between pDC reconstitution and the occurrence of GVHD show some conflicting data [38]. Relatively low pDC levels at days 0 to 60 after HCT are associated with moderate to severe aGVHD in children, which is in line with observations in adults [54][55][56].…”
Section: Dendritic Cellsmentioning
confidence: 63%
See 1 more Smart Citation
“…Previous studies have analyzed the association of DCs with the complex pathophysiology of GVHD with controversial results: some studies in mice have shown that pDC or mDCs may initiate aGVHD whereas others have shown that pDC may protect against aGVHD [33][34][35]. In the clinical setting, all series, including ours, showed that a low DC counts in the PB after transplantation are consistently associated with a higher incidence of aGVHD both in adults and in children [13,15,16,24,36]. In our series, we observed that pDC counts in the graft had an opposite effect on GVHD to that of pDC counts in the PB.…”
Section: Discussionmentioning
confidence: 74%
“…Of note, strategies exploiting donor cDCs in the setting of allogeneic SCT merit consideration, since relapse-free survival after allogeneic SCT was correlated with higher counts of donor cDC and pDC per µL of peripheral blood in a cohort comprising pediatric AML and myelodysplastic syndrome patients. This result suggests that expanding donor cDCs and/or pDCs for administration following SCT will enhance response rates [124]. In addition, the importance of host cDC in cross-presenting LAA was recently highlighted in a mouse model of post-transplant AML [125].…”
Section: Dc-based Immunotherapy In Leukemiamentioning
confidence: 99%